Unleashing Data Potential with Data Divinity: Framework for Efficient Fintech-BNPL Data Lake - Rathinasamy, Durga (Digital Repository of Theses - SSBM Geneva, 2023)
According to a recent Statista report by (Norrestad, 2022), the Fintech industry has experienced significant growth, with a 68% increase in Fintech startups from 2018 to 2021. Additionally, the global Fintech market is projected to grow at a compound annual growth rate (CAGR) of 23.58% from 2021 to 2025, as stated in the (81 Key Fintech Statistics 2021/2022: Market Share & Data Analysis, n.d.). This rapid growth is expected to lead to a surge in digital transactions within a short period. In order to effectively compete and make strategic business decisions with a wide range of insights, it is essential for Fintech companies to establish and maintain foolproof Cloud Data Lakes. However, building and managing a data lake has become problematic due to inappropriate management decisions, non-strategic approaches, technical solutions, and inefficient governance. To address these challenges and their impact on the Fintech business, this research paper aims to propose a conceptual framework and strategies for identifying pain points in building a cloud data lake within the Fintech industry, specifically to BNPL - Buy-Now-Pay-Later. The proposed framework will offer a comprehensive 360º view for managing constraints in Fintech-BNPL dthe ata lake.